Efektivitas Izin Pertambangan Emas Rakyat di wilayah Ratatotok Sulawesi Utara Terhadap Pertambangan Emas Ilegal - Reginaldy, Brandon; Yusuf, Rayhan; Rahmania, Nadhila Viryanda; Nadifa, Shafina; Husain, Faisal Purnama (UI Scholars Hub, 2025)
Mining represents one of the government's initiatives aimed at fostering employment opportunities and, moreover, constitutes a crucial component of the broader strategy to foster community autonomy and resilience in meeting the basic necessities of life. The concept of community-based gold mining refers to a mining system that provides the management of mining sites to the local community for the purpose of gold extraction. Gold is a metal with a relatively high economic value, utilized in a multitude of ways, including as jewelry and as an investment. However, it is important to note that not all areas possess the requisite conditions for gold mining. This is exemplified by the Ratatotok area, situated on the south coast of North Sulawesi Island, which boasts a plethora of natural resources, including substantial mining potential. The implementation of this initiative is hindered by the presence of illegal gold mining operations, driven by the economic necessity of those who are unemployed or impoverished. This has led to a situation where many individuals in Ratatotok have resorted to opening illegal mines on community-owned land in order to generate immediate profits. This article will further examine the effectiveness of the People's Gold Mining License in Ratatotok, North Sulawesi, in preventing illegal gold mining in accordance with Law Number 3 of 2020. In order to ascertain the efficacy of measures taken to prevent the emergence of illegal gold mining in Ratatotok, it is necessary to adopt a normative juridical approach. This entails conceptualising the law as the written legislation or rules and norms that serve as a benchmark for human behaviour deemed appropriate.